COVID-19: Autopsy findings in six patients between 26 and 46 years of age. (July 2021) - Greuel, Selina; Ihlow, Jana; Dragomir, Mihnea-Paul; Streit, Simon; Corman, Victor Max; Haberbosch, Linus; Winkler, David; Meinhardt, Jenny; Aschman, Tom; Schneider, Julia; Trotsyuk, Iryna; Kunze, Catarina Alisa; et al.
Highlights: Pre-existing medical conditions increase the risk of fatal COVID-19 in younger adults. Younger and healthy COVID-19 patients may develop serious health conditions. Younger COVID-19 patients are prone to thromboembolic complications. Abstract: Objectives: Studies on coronavirus disease 2019 (COVID-19) usually focus on middle-aged and older adults. However, younger patients may present with severe COVID-19 with potentially fatal outcomes. For optimized, more specialized therapeutic regimens in this particular patient group, a better understanding of the underlying pathomechanisms is of utmost importance. Methods: Our study investigated relevant, pre-existing medical conditions, clinical histories, and autopsy findings, together with SARS-CoV-2-RNA, determined by qPCR, and laboratory data in six COVID-19 decedents aged 50 years or younger, who were autopsied at the Charité University Hospital. Results: From a total of 76 COVID-19 patients who underwent an autopsy at our institution, six (7.9%) were 50 years old or younger. Most of these younger COVID-19 decedents presented with pre-existing medical conditions prior to SARS-CoV-2 infection. These included overweight and obesity, arterial hypertension, asthma, and obstructive sleep apnea, as well as graft-versus-host disease following cancer and bone marrow transplantation. Furthermore, clinical histories and autopsy results revealed a disproportionally high prevalence of thromboembolism and ischemic organ damage in this patient cohort. Histopathology and laboratory results indicated coagulopathies, signs of immune dysregulation, and liver damage. Conclusions: In conclusion, pre-existing health conditions may increase the risk of severe and fatal COVID-19 in younger patients, who may be especially prone to developing thromboembolic complications, immune dysregulation, and liver damage.